Genetic and phenotypic diversity in a germplasm working collection of cultivated tropical yams (Dioscorea spp.) - Sartie, A.M.; Asiedu, Robert; Franco, J. (Springer, 2012)
A working collection of yam (Dioscoreaspp.) comprising 53 landraces and seven improved cultivars of four species (D. alata L., D. cayenensis Lam., D. dumetorum (Kunth) and D. rotundata Poir.) was evaluated for phenotypic and genetic diversity. The evaluation involved field assessment of 24 morphological traits and DNA analysis with 32 Simple sequence repeat (SSR) polymorphic markers. Diversity was greater between species than within species; highest in D. rotundata and lowest in D. alata and D. cayenensis. Analysis based on combined phenotypic and SSR marker data sets revealed a close relationship between D. rotundata and D. cayenensis, but D. alata and D. dumetorum remained as distinct species. D. alata was related genetically to D. rotundata and D. cayenensis, but phenotypically to D. dumetorum. The study showed that cultivars obtained from different farmers may bear the same name but be genetically different. Polymorphic SSR markers were identified that may be used for genetic analysis across yam species. The working collection assessed in this study represents a good gene pool for intra- and inter-specific hybridization in yam genetic improvement.